2014
DOI: 10.1097/brs.0000000000000321
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Cervical Spine Diagnosis on the Careers of National Football League Athletes

Abstract: This study suggests that athletes with preexisting cervical spine pathology were less likely to be drafted than controls. Players with preexisting cervical spine pathology demonstrated a shorter career than those without; however, statistically based performance and numbers of games started were not different. Players with cervical spinal stenosis and those with a history of previous surgery demonstrated no difference in performance-based outcomes and no reports of neurological injury during their careers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 16 publications
2
24
0
Order By: Relevance
“…The matching process in this study was very strict and is consistent with previously published studies. 10 , 11 However, it does not account for other preexisting injuries. Furthermore, variables such as the coaching scheme and the presence of more skilled players on a team’s roster may significantly alter a player’s playing time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The matching process in this study was very strict and is consistent with previously published studies. 10 , 11 However, it does not account for other preexisting injuries. Furthermore, variables such as the coaching scheme and the presence of more skilled players on a team’s roster may significantly alter a player’s playing time.…”
Section: Discussionmentioning
confidence: 99%
“…A previously established and validated Performance Score was calculated for all players excluding offensive linemen, kickers, and punters to compare on-field statistics from 1 athlete to another and from 1 position to another. 3 - 5 , 9 - 11 , 13 …”
Section: Methodsmentioning
confidence: 99%
“…Of the 32 studies, 30 were injury specific. There were 2 studies on cervical spine injuries, 30 , 35 5 on foot injuries, 7 , 23 , 25 , 37 , 38 1 on hand injuries, 26 4 on hip/groin injuries, 14 , 17 , 18 , 33 9 on knee injuries, 2 , 8 , 9 , 13 , 21 , 22 , 24 , 31 , 32 3 on lumbar spine injuries, 27 , 29 , 34 and 6 on shoulder injuries. 10 , 11 , 15 , 16 , 19 , 28 No studies specifically examined injuries of the ankle, elbow, or long bones.…”
Section: Resultsmentioning
confidence: 99%
“…Schroeder et al 13,14 concluded that although there was a significant difference in career longevity, there was no difference in career performance for those athletes with pre-existing cervical or lumbar spine conditions compared to controls. Although these authors assessed career performance, our findings are in contrast to theirs, as we found linebackers with a prior history of spinal injury had significantly poorer performance than their controls, recording fewer games started ( P = .014), fewer mean tackles ( P = .048), and fewer tackles for a loss ( P = .033).…”
Section: Discussionmentioning
confidence: 99%